Kappa-Opioid Agonist U50,488H-Mediated Protection Against Heart Failure Following Myocardial Ischemia/Reperfusion: Dual Roles of Heme Oxygenase-1 - Guang Tong; Ben Zhang; Xuan Zhou; Jinbo Zhao; Zhongchan Sun; Ye Tao; Jianming Pei; Weida Zhang (Cellular Physiology and Biochemistry, 2016)
Backgrounds/Aims: The selective κ-opioid agonist U50,488H protects heart from myocardial ischemia-reperfusion (MI/R) injury. We examined whether U50,488H is also beneficial for MI/R induced heart failure. Methods: Anesthetized male Sprague-Dawley rats were subjected to 30 min of myocardial ischemia via left anterior descending coronary artery (LAD) occlusion, followed by 4 weeks of reperfusion. Infarct size was examined by Evans blue/triphenyl tetrazolium chloride (TTC) staining. Cardiac function and remodeling were examined by echocardiography and histology. HO-1 gene transcription and expression were measured by RT-PCR and western blot. Results: Compared to vehicle-treated MI/R rats, rats administered a single dose of U50,488H at the beginning of reperfusion exhibited reduced myocardial infarct size, oxidative stress, hypertrophy, and fibrosis, improved mechanical function, and greater neovascularization. U50,488H also increased myocardial heme oxygenase (HO)-1 gene transcription and expression, while pharmacological HO-1 inhibition reversed all protective effects of U50,488H. Furthermore, U50,488H protected control cultured cardiomyoctes against simulated I/R-induced apoptosis but not cultures subjected to shRNA-mediated HO-1 knockdown. Inhibition of HO-1 in the subacute phase of reperfusion reversed the U50,488H-induced increase in neovascularization and suppression of oxidative stress. Finally, U50,488H increased Akt phosphorylation and nuclear translocation of Nrf2, a key HO-1 transcription activator, while inhibition of PI3K-Akt signaling abolished U50,488H-induced Nrf2 nuclear translocation, HO-1 upregulation, and cardioprotection. Conclusion: Activation of HO-1 expression through the PI3K-Akt-Nrf2 pathway may mediate the acute and long-term protective effects of U50,488H against heart failure by enhancing cardiomyocyte survival and neoangiogenesis and by reducing oxidative stress.